Calcium as a Plant Nutrient - Prasad, Rajendra; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2020)
Calcium (Ca) is an essential plant nutrient responsible for the integrity of cells and plant structure, yet it is generally neglected, because it is available in plenty in most cultivated soils. It is therefore not applied as a fertilizer to crops except in groundnut. In acid soils, where it is limiting, it is applied in large amounts as a soil amendment as lime. In sodic soil, where excess of Na creates problems in crop production Ca is applied as gypsum, another soil amendment. When applied in large amounts as lime or gypsum, Ca nutrition is already taken care of and thus there is no need of annual application as a fertilizer. Nevertheless its importance as a plant nutrient cannot be ignored.